Worm : The First Digital World War - Bowden, Mark, 1951- (U.K Grove Press, 2012)
Journalist Mark Bowden delivers a look at the ongoing and largely unreported war taking place literally beneath our fingertips. When the Conficker computer worm was unleashed on the world in November 2008, cybersecurity experts did not know what to make of it. Was it a platform for criminal profit, or a weapon? The worm, exploiting security flaws in Microsoft Windows, grew at an astonishing rate, infecting millions of computers around the world within weeks. Once the worm infiltrated one system it was able to link that system with others to form a single network under illicit outside control, a situation known as a "botnet," soon capable of overpowering any of the vital computer networks that today control banking, telephone service, energy flow, air traffic, health-care information, even the Internet itself. This book reports on the battle between those determined to exploit the Internet and those committed to protect it.--From publisher description.
Keywords: Computer viruses -- Cyberterrorism -- Computer crimes